2019
DOI: 10.1002/jor.24301
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Book‐Type Acellular Bone Scaffold and Fibrocartilage Scaffold for Bone‐Tendon Healing

Abstract: Bone-tendon (B-T) healing is a clinical challenge due to its limited regeneration capability. Fibrocartilage regeneration and bone formation at the healing site are two critical factors for B-T healing. Promoting fibrocartilage regeneration and bone formation by tissue-engineering may be a promising treatment strategy. In this study, we innovatively fabricated two kinds of acellular scaffolds from bone or fibrocartilage tissues, namely the book-type the acellular bone scaffold (BABS) and the book-type acellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…When evaluating the overall effect of postoperative exercise using an ANOVA, mice from treadmill group had significantly higher BV/TV results compared with mice received free cage recovery (Figure 2B). SR‐μCT provides a novel method to visualize the fibrocartilage in enthesis with phase retrieval imaging 28 . After 3D reconstruction, the fibrocartilage layer can be easily distinguished (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating the overall effect of postoperative exercise using an ANOVA, mice from treadmill group had significantly higher BV/TV results compared with mice received free cage recovery (Figure 2B). SR‐μCT provides a novel method to visualize the fibrocartilage in enthesis with phase retrieval imaging 28 . After 3D reconstruction, the fibrocartilage layer can be easily distinguished (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…SR-μCT provides a novel method to visualize the fibrocartilage in enthesis with phase retrieval imaging. 28 After 3D reconstruction, the fibrocartilage layer can be easily distinguished ( Figure 2C). Quantitatively in coronal plane images, fibrocartilage lacunae are easily characterized in the fibrocartilage layer by synchrotron radiation μCT with a spatial resolution of 3.25 µm ( Figure S3).…”
Section: Temporal Expression Of Periphery Neuropeptidesmentioning
confidence: 99%
“…9,25,38 In order to transform the difficult healing of 2 entirely different tissues (bone to tendon) to much easier homogeneous tissue healing (tendon-tendon and bone-bone), a book-shaped engineered TFBC was invented, 16 which has shown potential for rotator cuff repair. 9,26,32,39 In addition, TFBC includes the natural fibrocartilage zone, which is difficult to regenerate after rotator cuff injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rabbit partial patellectomy model, both BAFS and BABS can promote tendon-bone healing, while the BAFS was more conductive in tendon-bone healing than the BABS. This study may provide a valuable reference for screening the optimal tissue-engineering scaffold applied in tendon-bone healing (Lu et al, 2019).…”
Section: Natural Materialsmentioning
confidence: 99%
“…Acellular scaffolds play a unique role in promoting tendon bone healing. Lu et al, 2019 found an appropriate decellularization protocols for fibrocartilage tissue and prepared a novel book-shaped acellular fibrocartilage scaffold with cell-loading capability and chondrogenic inducibility for tissue-engineered fibrocartilage and bone-tendon healing. This screened scaffold alone could induce endogenous cells to satisfactorily regenerate fibrocartilage at 16 weeks, as characterized by fibrocartilaginous ECM deposition and good interface integration and may have further broad clinical applications in promoting bone-tendon healing.…”
Section: Natural Materialsmentioning
confidence: 99%